2021
DOI: 10.3390/pharmaceutics13040487
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Absorption Rate and Extent Enhancement of Black Ginseng (CJ EnerG) over Red Ginseng in Healthy Adults

Abstract: Red ginseng (RG) and black ginseng (BG, CJ EnerG) were prepared from fresh ginseng using one and nine cycles of steaming and drying, respectively. This process reduces the molecular weight (MW) of ginsenoside-active compounds in ginseng by removing sugar moieties from their dammaranes. We compared the pharmacokinetic characteristics of ginsenosides between BG comprising mainly low-MW ginsenosides (Rg3, Rg5, Rk1, and Rh1) and RG that predominantly contains high-MW ginsenosides (Rb1, Rb2, Rc, Rd, Re, and Rg1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Kim et al [ 72 ] reported that the plasma AUCs of GRd, GRg3, GF2, and CK were correlated with the intake amount of these ginsenosides in humans. Additionally, plasma concentrations of GRg3 after the oral intake of black ginseng, which contains a higher amount of GRg3 than RGE, were significantly higher than that after oral intake of RGE in human [ 73 ]. Contrary to the case of GRg3, GRh1 and GRh2 was not detected in the plasma from mice supplemented with LAB.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 72 ] reported that the plasma AUCs of GRd, GRg3, GF2, and CK were correlated with the intake amount of these ginsenosides in humans. Additionally, plasma concentrations of GRg3 after the oral intake of black ginseng, which contains a higher amount of GRg3 than RGE, were significantly higher than that after oral intake of RGE in human [ 73 ]. Contrary to the case of GRg3, GRh1 and GRh2 was not detected in the plasma from mice supplemented with LAB.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal concentration of Rg5 in the blood of human subjects taking ginseng orally at a dose of 9 g was 2−10 nM [44]. Ginsenoside Rg5 protected neuronal cells from glutamate−induced apoptosis in an in vitro Huntington's disease assay at a concentration of 1000 nM [32] and exhibited a neuroprotective effect in heat stress−induced apoptosis at concentrations of 26−52 μM in experiments with murine hippocampal neuronal HT22 cells, but was toxic at concentrations of 78−104 μM [33].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro studies on isolated cells have been conducted to uncover the molecular mechanisms of action of ginseng extracts and isolated ginsenosides (Supplemental Table S1 in Supplement 1). However, the concentrations of ginsenosides and the extracts used in these studies [32][33][34][35][36][37][38][39][40][41][42][43] were incompatibly higher than those detected in pharmacokinetic (PK) studies in humans [44,45] and animals orally administrated with ginseng preparations at the highest therapeutic doses [46][47][48][49][50][51] (Supplemental Table S2 in Supplement 1).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As a matter of fact, the blood cells and tissues are continuously exposed to varying concentrations of ginsenosides after oral administration of ginseng in the daily therapeutic doses of 0.6-9.0 g [10,29,30]. They range from maximal detected concentrations of 35 ng/ml to the limit of detection 0.5 ng/ml and less within 12-48 h after oral intake [29]. A recent study demonstrated that ginsenoside Rg5 exhibits soft-acting effects in a wide range of physiological and sub-physiological concentrations from 1 μM to 1 aM.…”
Section: Introductionmentioning
confidence: 99%